Chronic myelomonocytic leukemia mimicking hematologic systemic lupus erythematosus. (February 2017) - Moura, C A; Santiago, M; Neto, J; Gomes de Souza, V H; Moura, C Geraldo
The relationship between primary hematologic disease and rheumatologic manifestations is well known, especially acute lymphocytic leukemia, lymphomas, plasma cell dyscrasias and myelodysplastic syndrome (MDS). Currently, more has been described about autoimmune manifestations in chronic myelomonocytic leukemia (CMML). Many different clinical scenarios may lead a patient with MDS/CMML initially to seek a rheumatological unit. Autoimmune features such as polymyalgia rheumatic symptoms, myositis, neutrophilic dermatosis, cutaneous vasculitis and positive antinuclear antibodies (ANA) are some examples of clinical presentation of MDS/CMML. Moreover, peripheral cytopenias are a common initial presentation both for systemic lupus erythematous (SLE) and MDS/CMML. The aim of this study was to describe a case of an elderly woman with thrombocytopenia and positivity of antibodies to anti-extractable nuclear antigens (anti-ENA) as initial manifestation of CMML mimicking SLE, and to present some clues that encourage the clinician to perform a bone marrow study in such a clinical scenario.